Perception of teacher interpersonal behavior and EFL achievement - Horvacki Mirjana (Array, 2013)
Starting from the hypothesis that FL achievement may be associated with the nature of teacher- student relationship (den Brok et al., 2001 ; Shuell, 1996), in this study we looked into learner perception of teacher interpersonal behaviour in the English as a foreign language (EFL) classroom as well as teacher self-perception of such behaviour. Using the Questionnaire on Teacher Interaction (QTI) (Wubbels, Créton and Hooymayers, 1985) and the end-of-the-semester grade in EFL, we aimed at establishing possible convergences and divergences of teachers’ and learners’ perceptions, the average interpersonal EFL teacher profile and the relationship between student EFL achievement and scores on the eight scales of the QTI (Leadership, Helpful/Friendly, Understanding, Student Responsibility/Freedom, Uncertain, Dissatisfied, Admonishing, Strict). Our sample included 463 Croatian secondary school EFL students and 19 EFL teachers. The results indicated a considerable amount of divergence between the perceptions of teachers and their learners. The average type of interpersonal behaviour pattern in the Croatian EFL classroom based on this sample was found to be somewhere between the Authoritative and Tolerant/Authoritative types. With respect to EFL achievement of students, when learner perceptions were used significant correlations were found between the eight scales of the QTI and end-of- the-semester English grade. Interpersonal teacher behaviour seemed to have a significant effect on student achievement, though primarily in terms of what individual learners perceived as important for themselves.